Understanding and manipulating the intrinsic point defect in α-MgAgSb for higher thermoelectric performance. Issue 43 (19th October 2016) - Liu, Zihang; Geng, Huiyuan; Mao, Jun; Shuai, Jing; He, Ran; Wang, Chao; Cai, Wei; Sui, Jiehe; Ren, Zhifeng
Abstract : Thorough first-principles calculations reveal that an Ag vacancy is the dominant intrinsic point defect in α-MgAgSb. Point-defect engineering can be realized via rationally controlling the hot press temperature due to the recovery effect. Abstract : Nanostructured α-MgAgSb has been demonstrated as a good p-type thermoelectric material candidate for low temperature power generation. Nevertheless, the intrinsic defect physics that impedes further enhancement of its thermoelectric performance is still unknown. Here we first unveil that an Ag vacancy is a dominant intrinsic point defect in α-MgAgSb and has a low defect formation energy, shown by first-principles calculations. In addition, the formation of an Ag vacancy could increase the crystal stability. More importantly, intrinsic point defects, namely an Ag vacancy, can be rationally engineered via simply controlling the hot press temperature, due to the recovery effect. Collectively, a high peak ZT of ∼1.3 and average ZT of ∼1.1 are achieved when hot pressed at 533 K. These results elucidate the pivotal role of intrinsic point defects in α-MgAgSb and further highlight that point defect engineering is an effective approach to optimize the thermoelectric properties.